2015
DOI: 10.1088/1674-1056/24/8/080701
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling of oscillating GHz electric field influence on the kinesin affinity to microtubule

Abstract: Kinesin is a microtubule-associated motor protein which can respond to the external electric field due to its polarity. Using a molecular dynamics simulation method, the effect of such a field on the affinity of kinesin to the αβ-tubulin is investigated in this study. To consider kinesin affinity, the system is exposed to an electric field of 0.03 V/nm with frequency values of 1, 2, …, 9, and 10 GHz. It is found that the applied electric field can change kinesin affinity to the microtubule. These changes could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Due to the dynamic nature of this field, the sample experiences electric field components, both, perpendicular as well as parallel to the sample surface. A similar effect of an external rf electric field on weak dispersive bonding has been reported for biomolecules 38 .…”
Section: Discussionsupporting
confidence: 75%
“…Due to the dynamic nature of this field, the sample experiences electric field components, both, perpendicular as well as parallel to the sample surface. A similar effect of an external rf electric field on weak dispersive bonding has been reported for biomolecules 38 .…”
Section: Discussionsupporting
confidence: 75%
“…Electric fields have also been shown to disrupt MT polymerization, which is exploited as the mechanism of action of tumor treating fields (TTFields) that use low-magnitude (<2.5 V/cm) fields applied at 100−300 kHz [122]. Molecular dynamics simulations also indicate that electric fields of GHz frequencies can disrupt tubulin and tubulin associated proteins [123][124][125]. Adding to the existing literature on MT dynamics under electric fields, recent molecular dynamics studies and experimental studies now demonstrate that PEFs can directly disrupt MTs.…”
Section: Microtubules-direct Mechanismsmentioning
confidence: 99%
“…Although there are several experimental [28] , [30] , [31] , [32] and theoretical works [21] , [23] , [33] demonstrating, for example, that an EF can affect the structure of tubulin and microtubules (MTs) [23] and can be used to steer MTs in kinesin gliding assays [11] , little is known about the direct effect of an external EF on kinesin itself. Molecular dynamics simulations, in which EF and mechanical pull were combined, have shown that an intense oscillating EF (up to 10 GHz) affects (mostly decreases) the affinity of kinesin toward tubulin [34] , [35] . In our recent preliminary work [36] , we demonstrated that under the influence of a static EF with a duration of several tens of nanoseconds, the kinesin dipole and contact surface area with the tubulin dimer were affected.…”
Section: Introductionmentioning
confidence: 99%